Fixed and removable orthodontic retainers, effects on periodontal health compared: A systematic review - Vincenzo Quinzi; Elisabetta Carli; Alessandra Mummolo; Federica De Benedictis; Simone Ettore Salvati; Gianluca Mampieri (Journal of Oral Biology and Craniofacial Research)
The aim of this systematic review is to analyze the properties of the different types of orthodontic retainers, identify their differences and define which type of device is most effective and less harmful to periodontal health. Methods: A literature search was carried out by a reviewer by consulting PubMed, Lilacs, Embase, Medline full text, Scopus, Web of Science, Cochrane library, and Science Direct electronic databases for biomedical and health literature as well as the grey literature and setting up the search from December 2010 without any restriction about articles languages. Results: The results showed that patients who wear retainers for a long period have significant differences in clinical parameters compared to patients without retainers. The type of retainer chosen also significantly influences the overall periodontal health of patients. Fixed retainers, both glass-fibre reinforced and steel wire retainers, proved to be the retainer type with the highest plaque and calculus accumulation values compared to removable retainers. In addition, among fixed retainers, glass-fibre reinforced retainers proved to be those that mostly promote the plaque and calculus accumulation in the application site. Conclusion: Fixed retainers are the best devices to maintain the alignment of mandibular anterior teeth in the long term. Among these devices, stainless steel lingual retainers, plain or braided, should remain the first choice. Although they are also susceptible to periodontal complications, their effect on periodontal health can be considered statistically insignificant if compared to glass-fibre reinforced retainers which, showing worse periodontal complications, should not be used.